Eferocitose na presença de PAMP estimula ativação de macrófagos de perfil misto M1/M2 - Salina, Ana Carolina Guerta [UNESP] (2015)
The phagocytosis of apoptotic cells is dynamic and crucial for homeostasis after injury. Macrophages act on the clearance of apoptotic cells and collaborate with defense against microorganisms. There are at least two distinct macrophage populations classified as M1 macrophages (pro-inflammatory) and M2 macrophages (anti-inflammatory). Both cells differ on the state of polarization and effectors function depending primarily on the microenvironment and microorganisms that interact into the tissue. In a situation of sterile lung injury (inhalation of toxic agents), there are accumulation of apoptotic cells without the presence of pathogen. On the other hand, during a bacterial pulmonary infection there is intense cell migration to the infection site in an attempt to impair bacterial growth, resulting in a large accumulation of infected-apoptotic cells in the tissue. Therefore, this study has evaluated in vitro and in vivo, the effect of the phagocytosis of infected-apoptotic cells (AC-Sp) or sterile cells (AC) on the polarization of M1/M2 macrophages, as well as in their effector functions and the effect of PGE2 in the context of efferocytosis. M0 macrophages co-cultured with AC or AC-Sp show an intermediate phenotype between M1 and M2 with high secretion levels of IL-6, TNF-α, PGE2, NO and TGF-β, and gene expression profile related to M1, iNOS, and M2, arginase 1. Furthermore, M0 macrophages cultured with AC or AC-Sp show strong suppression of the macrophage microbicidal function when challenged with S. pneumonia. The presence of PGE2 drives the polarization of M0 macrophages to a M2 profile, and in the presence of COX inhibitors, it reverses the polarization of this macrophage phenotype. The in vivo results demonstrate that the instillation of AC or AC-Sp promotes distinct microenvironments in the lungs of these animals, which influence the resolution of the infection. All these results suggest that the presence of AC or AC-Sp promotes, ...